Assessment of Inhalation Techniques in COPD and Asthma Patients using Metered Dose Inhaler and Rota-haler - Suthar, Jalpa; Patel, Zalak A; Shelat, Bhavik (Indian Journal of Pharmacy Practice)
Background: Inhaler dosage forms are cornerstone therapy in respiratory disease. Inhalers are principle vehicles for effective administration of medication. The effectiveness of inhalation drugs can affect by factors including age, gender, education status, duration of disease, type of inhaler used and correct inhalation technique. Objectives: To assess Inhalation Technique in the patients of COPD and Asthma using MDI and Rota-haler. Study prescribing trend of patient of COPD and Asthma. Methods: A prospective, interventional study conducted in Medical Outpatient Department of Sheth HJ Mahagujarat Hospital, Nadiad. Patients were diagnosed with asthma and COPD using MDI and Rota-haler inhalers. Total 60 patients were included in the study; Patients’ history was recorded and after explanation of procedure for inhalers; assessments of inhalation technique were evaluated in inhaler specific checklist described by Dutch Asthma Foundation. Results: Total 53.39% (Asthma) and 58.35% (COPD) users used inhaler incorrectly. In Asthma MDI; it shows clinical significance but statistically non-significant (p=0.10) and Rota-haler; shows both clinical and statistical significance (p=0.01). In COPD MDI (p=0.02) and Rota-haler (0.04); shows both clinical and statistical significance (p=0.02). It shows improvement in patients’ performance after providing information on use of inhaler. The most commonly prescribed drugs with MDI and Rota-haler were Short acting β-agonist, Corticosteroids and Combination of Bronchodilator and Corticosteroids. Conclusion: Majority of patients in Asthma (53.39%) and COPD (58.35%) used inhaler incorrectly which leads to decrease in efficacy and drug delivery, increased side effects and economic burden with non-compliance. Post-Intervention use on inhalation technique showed improvement.
Keywords: Chronic Obstructive Pulmonary Disease; Asthma; Metered Dose Inhaler; Dutch Asthma Foundation; Rota-haler.